Association of vitamin D status at birth and respiratory outcomes in preterm infants - Park, Sook-Hyun (Clinical and experimental pediatrics, 2019)
Vitamin D deficiency increases the loss of innate and adaptive immune function and susceptibility of autoimmune disease and infection, which results in an association with higher risk of sepsis, milk sensitization, respiratory infection or wheeze, type 1 diabetes, multiple sclerosis, and cardiovascular diseases [1]. The major determining factor of neonatal vitamin D level at birth is maternal vitamin D status, as vitamin D transfers to the fetus during third trimester; this suggests that preterm infants are at higher risk of vitamin D deficiency than full-term infants. [...]vitamin D status at birth may be associated with respiratory morbidities; thus, further studies should be needed to identify the optimal dose and duration of vitamin D supplementation to improve respiratory outcomes in Korean preterm infants.